STUDI KASUS PROSEDUR PEMERIKSAAN LOPOGRAFI PADA KASUS CA RECTUM DI INSTALASI RADIOLOGI RSPAU dr. S. HARDJOLUKITO - Wati, Retno; Gemilang , Anjas Fitria; Mukmin, Amril; MN, Ildsa Maulidya (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The lopographic examination procedure according to Bontrager, et al., (2014), Ballinger (2012), and Mulyati and Walidaeni (2019) uses Antero Posterior (AP), Lateral, Right Posterior Oblique (RPO), and Left Posterior Oblique (LPO) projections. Contrast media according to Bontrager, et al., (2014) and Kundagluwar, et al., (2016) barium sulfate, while at RSPAU dr. S. Hardjolukito AP and lateral projection, water soluble contrast media. This study aims to determine the procedure for lopographic examination in cases of rectal ca, the reasons for using water soluble contrast media and the reasons for using AP and lateral projections. This research is a qualitative descriptive case study approach at the Radiology Installation of RSPAU dr. S. Hardjolukito. Data collection starts from December 2022 to July 2023. Data collection is carried out by observation, documentation, interviews and literature. The research subjects were three radiographers and one radiologist. Data analysis namely data reduction, data presentation and drawing conclusions. The results of the study showed that the lopographic examination procedure for cases of rectal cavities began with special preparations the day before the examination on a low-fiber diet, administration and fasting. Preparation of non-sterile and sterile materials, water soluble contrast media. Insert contrast media through the anus and stoma. The examination technique is BNO plain photo, AP post-contrast and Lateral post-contrast. The reason is that water soluble contrast media is easily absorbed by the body, easily excreted, and safe to use. The reason why the AP projection can see the entire colon is so that it can measure the distance from the tip of the rectum to the stoma. Lateral projection looks at the distance between the superior and inferior colon ends to be connected. It is recommended that a lopographic examination use a two-day low-fiber diet preparation, use fluoroscopy, colostomy equipment, and add RPO and LPO projections to see the flexures in order to increase the diagnostic value.